Community-level impacts of low-level diesel exposure on a natural cold-temperate/subarctic phytoplankton assemblage - Andreana M. Cadaillon; Irene R. Schloss; O. Magalí Olmedo-Masat; Michel Starr; Francesca Vidussi; Behzad Mostajir; Daniel Pech; Gustavo Ferreyra (Marine Pollution Bulletin, 2026)

Ticks Recovered from Opportunistically Examined Greater Grisons (Galictis vittata) in Veracruz, Mexico - Mariemma G. Escorcia-Quintana; Carlos D. Pérez-Brígido; Héctor M. Zazueta-Islas; Adair Caro-Macin; Marlene Solís-Cortés; Estefania Grostieta; Carlos I. Miranda-Caballero; Juan M. Pech-Canché; Víctor Sánchez-Cordero; Ángel Rodríguez-Moreno; Arturo Serrano-Solis; Celina Naval-Ávila; et al. (Acta Parasitologica, 2026)

Bioactive Extracts from Yucatán Marine Invertebrates as Modulators of Microalgal Dynamics - Dawrin Pech-Puch; Rita Pires; Bárbara A. Rebelo; Diana Grilo; Carlos Gonzáles-Salas; Susana Eunice Calva-Pérez; Susana M. Gomes; Harold Villegas-Hernández; Sergio Guillén-Hernández; Abel M. Forero; Jaime Rodriguez; Carlos Jiménez; et al. (Marine Biotechnology, 2026)
The marine environment is a rich source of bioactive compounds with a wide range of applications. In this study, 65 extracts from sponges, ascidians, and a gorgonian collected from the Yucatán Peninsula, Mexico, were evaluated for their modulatory effects on the growth of four microalgal species. Some extracts were found to exhibit pronounced algicidal activity, while others promoted growth. Bioassay-guided fractionation of the extract from Haliclona (Rhizoniera) curacaoensis led to the identification of arenosclerins A and C as potent algicidal agents, active across all tested microalgae. In contrast, the extract from Halichondria melanadocia enhanced microalgal growth, and chemical analysis revealed the presence of medelamine A and B as putative growth-promoting compounds. This study provides a new report on microalgae-modulating activities of marine sponge metabolites. The dual activity observed, both inhibitory and stimulatory, not only contributes to our understanding of marine compound diversity but also underscores the potential of these marine-derived compounds for sustainable environmental management practices.

Assessment of hydrogen sulfide exposure in shoreline cleanup workers during the 2025 Atlantic Sargassum bloom - R.E. Rodríguez-Martínez; S. Ramírez Said; M.A. Gómez-Reali; S. Rosales-Fuerte; J. Pech Figueroa; M. Costa; M.M. Veras (Harmful Algae, 2026)

Effects of domesticated-to-wild gene flow on the genetic structure and diversity of wild papaya (Carica papaya L.) in its Mesoamerican diversity area - Mauricio Heredia-Pech; Jaime Martínez-Castillo; Daniela A. Martínez-Natarén; Pedro Ruiz-Gil; Mónica I. Jiménez-Rojas; Matilde M. Ortiz-García; Mariana Chávez-Pesqueira (Genetica, 2025)

A data-driven approach to the processing of sniffer-based gas emissions data from dairy cattle - Peter Løvendahl; Viktor Milkevych; Rikke Krogh Nielsen; Martin Bjerring; Coralia Manzanilla-Pech; Kresten Johansen; Gareth F Difford; Trine M Villumsen (Computers and Electronics in Agriculture, 2024)

Effects of dietary supplementation of peanut skins (Arachis hypogaea) on performance, digestibility, and rumen fermentation of cattle: a meta-analysis - M. D. Idowu; Andres A. Pech-Cervantes; G. Taiwo; F. Eichie; Ibukun M. Ogunade; Z. M. Estrada-Reyes; Thomas H. Terrill (Tropical Animal Health and Production, 2023)

Multi-walled carbon nanotubes – zinc in commercial acrylic sealant as a coating for anticorrosive protection system in metallic building structures - D. Pech-Núñez; J. Gutiérrez; J. C. Cruz; R. E. Vega-Azamar; D. L. Trejo-Arroyo; M. P. Gurrola (European Journal of Environmental and Civil Engineering, 2023)

Pendrin abundance, subcellular distribution, and function are unaffected by either αENaC gene ablation or by increasing ENaC channel activity - Johannes Loffing; Vladimir Pech; Dominique Loffing-Cueni; Delaney C. Abood; Young Hee Kim; Chao Chen; Truyen D. Pham; Jill W. Verlander; Susan M. Wall (Pflügers Archiv - European Journal of Physiology, 2023)
The intercalated cell Cl − /HCO 3 − exchanger, pendrin, modulates ENaC subunit abundance and function. Whether ENaC modulates pendrin abundance and function is however unknown. Because αENaC mRNA has been detected in pendrin-positive intercalated cells, we hypothesized that ENaC, or more specifically the αENaC subunit, modulates intercalated cell function. The purpose of this study was therefore to determine if αENaC is expressed at the protein level in pendrin-positive intercalated cells and to determine if αENaC gene ablation or constitutively upregulating ENaC activity changes pendrin abundance, subcellular distribution, and/or function. We observed diffuse, cytoplasmic αENaC label in pendrin-positive intercalated cells from both mice and rats, with much lower label intensity in pendrin-negative, type A intercalated cells. However, while αENaC gene ablation within principal and intercalated cells of the CCD reduced Cl − absorption, it did not change pendrin abundance or subcellular distribution in aldosterone-treated mice. Further experiments used a mouse model of Liddle’s syndrome to explore the effect of increasing ENaC channel activity on pendrin abundance and function. The Liddle’s variant did not increase either total or apical plasma membrane pendrin abundance in aldosterone-treated or in NaCl-restricted mice. Similarly, while the Liddle’s mutation increased total Cl − absorption in CCDs from aldosterone-treated mice, it did not significantly affect the change in Cl − absorption seen with pendrin gene ablation. We conclude that in rats and mice, αENaC localizes to pendrin-positive ICs where its physiological role remains to be determined. While pendrin modulates ENaC abundance, subcellular distribution, and function, ENaC does not have a similar effect on pendrin.

Lupeol acetate isolated from Chrysophyllum cainito L. fruit as a template for the synthesis of N -alkyl-arylsulfonamide derivatives and their synergistic effects with metronidazole against Trichomonas vaginalis - Angel D. Herrera-España; Julio A. Aguiar-Pech; M. Elizbeth Alvarez-Sánchez; Victor E. Arana-Argáez; Cynthia K. Palomar-Gómez; Armin G. Jiménez-Ross; David Cáceres-Castillo; Rubén M. Carballo; Julio C. Torres-Romero (Natural Product Research, 2022)

Physiological factors facilitating the persistence of Pocillopora aliciae and Plesiastrea versipora in temperate reefs of south-eastern Australia under ocean warming - Raúl A. González-Pech; David J. Hughes; Paige Strudwick; Brett M. Lewis; David J. Booth; Will F. Figueira; Brigitte Sommer; David J. Suggett; Jennifer Matthews (Coral Reefs, 2022)
High-latitude reefs are suboptimal coral habitats, but such habitats are increasingly considered to be potential refugia from climate change for range-shifting coral reef species. Notably, tropical reef fish have been observed along the south-east coast of Australia, but their establishment on temperate rocky reefs is currently limited by winter minimum temperatures and other resource needs, such as structurally complex habitats typical of tropical reefs. Recent expansion of the branching subtropical coral Pocillopora aliciae in rocky reefs near Sydney (34° S) could diversify the architectural structure of temperate marine environments, thereby providing potential shelter for tropical reef taxa in warming seas. Here, we investigated whether future environmental conditions ( i.e. temperature increase) can influence the dominance of the subtropical branching coral P. aliciae over the resident encrusting coral Plesiastrea versipora in coastal Sydney by characterising physiological ( e.g. metabolic stability) and behavioural ( e.g. interspecific competitive hierarchy) traits that contribute to their competitive fitness. Our results suggest that a metabolic response, mediated by sterol and lipid metabolic pathways and provision of antioxidants, allows P. aliciae to reduce cellular stress and withstand exposure to short-term increased temperature. Conversely, P. versipora was more susceptible to heat exposure with no metabolic mediation observed. While P. versipora displayed greater aggressive behaviour when in direct contact with P. aliciae under all temperature conditions, the superior physiological and metabolic flexibility under increased temperatures of P. aliciae suggests that this species will likely outperform P. versipora under future increased temperatures. Such contrasting responses to environmental change would facilitate shifts in coral community and functional composition that could support further tropicalisation of coastal New South Wales.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Effects of a Light Crude Oil Spill on a Tropical Coastal Phytoplankton Community - Sébastien Putzeys; Miryam Juárez-Fonseca; Sonia S. Valencia-Agami; Armando Mendoza-Flores; Daniel Cerqueda-García; Ana C. Aguilar-Trujillo; Manuel E. Martínez-Cruz; Yuri B. Okolodkov; Flor Arcega-Cabrera; Jorge A. Herrera-Silveira; M. Leopoldina Aguirre-Macedo; Daniel Pech (Bulletin of Environmental Contamination and Toxicology, 2022)

The worm burden of tracer kids and lambs browsing heterogeneous vegetation is influenced by strata harvested and not total dry matter intake or plant life form - P. R. Jaimez-Rodríguez; P. G. González-Pech; J. Ventura-Cordero; D. R. B. Brito; L. M. Costa-Júnior; C. A. Sandoval-Castro; J. F. J. Torres-Acosta (Tropical Animal Health and Production, 2019)

The cell wall proteome from two strains of Pseudocercospora fijiensis with differences in virulence - Yamily Y. Burgos-Canul; Blondy Canto-Canché; Maxim V. Berezovski; Gleb Mironov; Víctor M. Loyola-Vargas; Ana Paulina Barba de Rosa; Miguel Tzec-Simá; Ligia Brito-Argáez; Mildred Carrillo-Pech; Rosa Grijalva-Arango; Gilberto Muñoz-Pérez; Ignacio Islas-Flores (World Journal of Microbiology and Biotechnology, 2019)

2‐Tridecanone impacts surface‐associated bacterial behaviours and hinders plant–bacteria interactions - Isabel M. López‐Lara; Joaquina Nogales; Ángel Pech‐Canul; Nieves Calatrava‐Morales; Lydia M. Bernabéu‐Roda; Paloma Durán; Virginia Cuéllar; José Olivares; Laura Alvarez; Diana Palenzuela‐Bretones; Manuel Romero; Stephan Heeb; et al. (Environmental Microbiology, 2018)
Summary Surface motility and biofilm formation are behaviours which enable bacteria to infect their hosts and are controlled by different chemical signals. In the plant symbiotic alpha‐proteobacterium Sinorhizobium meliloti , the lack of long‐chain fatty acyl‐coenzyme A synthetase activity (FadD) leads to increased surface motility, defects in biofilm development and impaired root colonization. In this study, analyses of lipid extracts and volatiles revealed that a fadD mutant accumulates 2‐tridecanone (2‐TDC), a methylketone (MK) known as a natural insecticide. Application of pure 2‐TDC to the wild‐type strain phenocopies the free‐living and symbiotic behaviours of the fadD mutant. Structural features of the MK determine its ability to promote S. meliloti surface translocation, which is mainly mediated by a flagella‐independent motility. Transcriptomic analyses showed that 2‐TDC induces differential expression of iron uptake, redox and stress‐related genes. Interestingly, this MK also influences surface motility and impairs biofilm formation in plant and animal pathogenic bacteria. Moreover, 2‐TDC not only hampers alfalfa nodulation but also the development of tomato bacterial speck disease. This work assigns a new role to 2‐TDC as an infochemical that affects important bacterial traits and hampers plant–bacteria interactions by interfering with microbial colonization of plant tissues.

Calcinea of the Red Sea: providing a DNA barcode inventory with description of four new species - Oliver Voigt; Dirk Erpenbeck; Rául A. González-Pech; Ali M. Al-Aidaroos; Michael L. Berumen; Gert Wörheide (Marine Biodiversity, 2017)

The ecology and management of mammal invasions in forests - A. David M. Latham; Bruce Warburton; Andrea E. Byrom; Roger P. Pech (Biological Invasions, 2017)

Landowners’ Perspectives on Coordinated, Landscape-Level Invasive Species Control: The Role of Social and Ecological Context - Rebecca M. Niemiec; Roger P. Pech; Grant L. Norbury; Andrea E. Byrom (Environmental Management, 2017)

Landholder participation in regional-scale control of invasive predators: an adaptable landscape model - A. S. Glen; M. C. Latham; D. Anderson; C. Leckie; R. Niemiec; R. P. Pech; A. E. Byrom (Biological Invasions, 2017)

Olfactory Response and Host Plant Feeding of the Central American Locust Schistocerca piceifrons piceifrons Walker to Common Plants in a Gregarious Zone - M A Poot-Pech; E Ruiz-Sánchez; H S Ballina-Gómez; M M Gamboa-Angulo; A Reyes-Ramírez (Neotropical Entomology, 2016)

Dominant predator odour triggers caution and eavesdropping behaviour in a mammalian mesopredator - Patrick M. Garvey; Alistair S. Glen; Roger P. Pech (Behavioral Ecology and Sociobiology, 2016)

Pervasive genetic structure at different geographic scales in the coral-excavating sponge Cliona vermifera (Hancock, 1867) in the Mexican Pacific - M. G. León-Pech; J. A. Cruz-Barraza; J. L. Carballo; L. E. Calderon-Aguilera; A. Rocha-Olivares (Coral Reefs, 2015)

Foraging Ermine Avoid Risk: behavioural responses of a mesopredator to its interspecific competitors in a mammalian guild - Patrick M. Garvey; Alistair S. Glen; Roger P. Pech (Biological Invasions, 2015)

Transfer of intracolonial genetic variability through gametes in Acropora hyacinthus corals - M. Schweinsberg; R. A. González Pech; R. Tollrian; K. P. Lampert (Coral Reefs, 2014)

Sociality in Euglossa (Euglossa) viridissima Friese (Hymenoptera, Apidae, Euglossini) - M. E. Cocom Pech; W. de J. May-Itzá; L. A. Medina Medina; J. J. G. Quezada-Euán (Insectes Sociaux, 2008)

Enhanced aerobic respiration improves in vitro coconut embryo germination and culture - A. E. Pech y Aké; R. Souza; B. Maust; J. M. Santamaría; C. Oropeza (In Vitro Cellular & Developmental Biology - Plant, 2004)

Cytometric determination of genome size in Colchicum species (Liliales, Colchicaceae) of the western Mediterranean area - A. Fridlender; S. Brown; R. Verlaque; M. Crosnier; N. Pech (Plant Cell Reports, 2002)

Expression of an antisense 1-aminocyclopropane-1-carboxylate oxidase gene stimulates shoot regeneration in Cucumis melo - M. B. Amor; M. Guis; A. Latché; M. Bouzayen; J.-C. Pech; J.-P. Roustan (Plant Cell Reports, 1998)